Adhesion of Epoxy Coating to Steel Reinforcement under Alkaline Conditions - Masoudi, Rana Jr (2013)
Epoxy-coated reinforcement was developed in the 1970s and became the primary corrosion protection technique in North America. Throughout the years, ECR has exhibited mixed results, with some regions and jurisdictions reporting good corrosion protection while others reported poor field performance of ECR. It has been established that epoxy coating can lose its adhesion in a wet environment thus providing poor corrosion protection of reinforcing steel. However, limited research has been done on the influence of concrete pore solution on adhesion of epoxy coating to reinforcing steel. This research investigates the effect of high alkali conditions on performance of ECR bars. Based on the test results, it was found that the rate of disbondment increases as the hydroxyl ion concentration increases and presence of high temperature accelerates the disbondment process.